Costos de producción en eventos deportivos de Downhill: Estudio de caso Super Downhill Mama Rumi, periodo 2022 - Pepe Aseicha, Karol Mishell (2025)
The present research entitled “PRODUCTION COSTS IN DOWNHILL SPORTS EVENTS: CASE STUDY SUPER DOWNHILL MAMA RUMI, PERIOD 2022”, aimed to establish the production costs of sporting events in Ecuador, as well as to determine the fixed costs and variable costs, applying the Cost, Volume, Profit Model of the Super Downhill Mama Rumi event. Therefore, each of the components that make up production costs such as materials, labor, indirect production costs, cost systems, volume-profit costs and break-even point were examined. Consequently, the study adopted a solid theoretical framework that supports the research and presents an analytical methodology to review the process of establishing the production cost budget. A mixed approach was used, which qualitatively analyzes the economic management method, and the level of research was descriptive, with the aim of establishing the mechanisms and processes in its execution. The results revealed the calculation of production costs determining the viability of the Downhill Mama Rumi event, for which information was collected from the organizers and codified in order to determine the viability of the event, subsequently the Cost, Volume and Benefit Model was applied to establish the main indicators such as break-even point, contribution margin and expected profit with which the possibilities that the event has to remain in the market were determined.